1991
DOI: 10.3109/00016489109127256
|View full text |Cite
|
Sign up to set email alerts
|

Audiological findings in elderly patients with chronic renal failure

Abstract: Effects of continuing nursing mode were studied in elderly home patients with chronic renal failure. Eighty five elderly patients with chronic renal failure were randomly divided into an experimental group (41 cases) and control group (43 cases). Patients in the control group were given the conventional discharge guidance and health education, and those in the experimental group were given the continuing nursing implemented by the continuing nursing team. The results showed that the scores on the self-care ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
13

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 35 publications
1
37
0
13
Order By: Relevance
“…Antonelli et al [1] reported that ABR wave latency was correlated to albumen and calcium levels. In addition, Pratt et al [8] reported changes in absolute and interpeak latency that were correlated to Ca ++ ion changes prior to and following hemodialysis.…”
Section: Pre-vs Post-hemodialysismentioning
confidence: 99%
See 2 more Smart Citations
“…Antonelli et al [1] reported that ABR wave latency was correlated to albumen and calcium levels. In addition, Pratt et al [8] reported changes in absolute and interpeak latency that were correlated to Ca ++ ion changes prior to and following hemodialysis.…”
Section: Pre-vs Post-hemodialysismentioning
confidence: 99%
“…[3] Studies using ABR as an index of auditory function among patients with end stage CRF showed evidence of various degrees of auditory dysfunction. Antonelli et al [1] compared pure tone thresholds and ABR wave latencies and interpeak latency differences of patients with end stage CRF undergoing hemodialysis to a control group of gender-and age-matched subjects with normal hearing, and to a second control group matched additionally by degree of hearing loss. They reported that pure tone hearing loss as well as wave I latency in the end stage CRF group was correlated with age and negatively correlated with serum albumin level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antonelli et al [35] found that patients with CRF had a significantly subclinical dysfunction of the VIII nerve caused by axonal uremic neuropathy. ADMA was found to contribute to the development of neuropathy, as lowering its level leads to an improvement in different nerve functions.…”
Section: Discussionmentioning
confidence: 99%
“…Worsening of hearing capacity has been attributed to vascular changes in the inner ear due to hyperlipidemia, ototoxic treatment, or recurrence of renal disease. 6 Sensorineural hearing impairment prevalence in pediatric transplant group was higher than in the chronic renal failure group (47% against 29%) in Mancini's study, and they found a significant correlation with the administration of ototoxic drugs after transplant (eg, aminoglycosides and furosemide). 7 Sensorineural hearing impairment prevalence was 62% in our patient group, and it was high when compared with the general population of children.…”
Section: Decibels Hertzmentioning
confidence: 99%